Development of an enzymatic pretargeting strategy for dual-modality imaging1. Issue 19 (7th March 2015) - Knight, J. C.; Mosley, M.; Stratford, M. R. L.; Uyeda, H. T.; Benink, H. A.; Cong, M.; Fan, F.; Faulkner, S.; Cornelissen, B.
<x xml:space="preserve">Abstract</x> An in vitro pretargeted imaging strategy based on the HaloTag enzyme is described. Dual-modality (SPECT and optical) HaloTag ligands enable the detection of HER2 expression.